Membandingkan Kompetensi Pustakawan Pendidikan dengan Pustakawan Pelatihan di Kabupaten Sidoarjo - Wicaksono, Moch Fikriansyah (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2018)
The library is an institution aims to provide information for its users. Whether its success or not it depends on the ability of a library manager. There are two types of librarians; librarians who had formal library education background and librarians who had library training background. Their difference competencies, resulting from different background, makes it interesting to explore. This research aims to compare librarians’ competencies who had difference background. The survey was conducted from May to June on both librarian’s type. The data then proceed using an independent sample t-test. The results of this test indicate that there are significant differences on their competencies, shows by independent value t-test less than 0.05, which is 0.000. This result shows that there are difference on core competencies between librarians who had formal library education background and librarians who had library training background. Considering libraries success depends on the manager’s ability to manage their human resource, it is important for libraries to choose librarians who have the right competencies to manage their school libraries.